Hepatoid adenocarcinoma of the colon. (16th April 2015) - Armaghani, Avan; Gonzalo, David Hernandez; Daily, Karen
Abstract : Hepatoid adenocarcinoma (HAC) is a rare extrahepatic adenocarcinoma that morphologically and immunophenotypically mimics hepatocellular carcinoma (HCC). We report the case of a 42-year-old woman with an extensive cancer history who presented with right-sided abdominal pain and lower gastrointestinal (GI) bleeding, and was ultimately diagnosed with colon adenocarcinoma. She underwent sigmoidectomy and adjuvant chemotherapy. Approximately 1 month after completion of chemotherapy, positron emission tomography showed presence of a 1.8 cm×1.4 cm mesenteric lymph node. She underwent treatment with chemotherapy and radiation followed by lymph node resection. Pathological findings from the lymph node were consistent with poorly differentiated carcinoma with hepatocellular differentiation. When compared with pathology from the colonic resection, both specimens showed histomorphological features and immunohistochemical profiles consistent with hepatocellular differentiation. Given these findings, a diagnosis of HAC of the colon with metastasis to a mesenteric lymph node was made.